2021
DOI: 10.1002/dad2.12149
|View full text |Cite
|
Sign up to set email alerts
|

The application of optical coherence tomography angiography in Alzheimer's disease: A systematic review

Abstract: Introduction: Discovering non-invasive and easily acquired biomarkers that are conducive to the accurate diagnosis of dementia is an urgent area of ongoing clinical research. One promising approach is retinal imaging, as there is homology between retinal and cerebral vasculature. Recently, optical coherence tomography angiography (OCT-A) has emerged as a promising new technology for imaging the microvasculature of the retina. Methods:A systematic review and meta-analysis was conducted to examine the applicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(67 citation statements)
references
References 75 publications
4
62
0
1
Order By: Relevance
“…However, the cerebral microvasculature is too small to be directly visualized in vivo . Due to the shared embryologic origin of the retina and brain, there is resemblance between blood-retinal barrier (BRB) and blood-brain barrier (BBB), and the retina is thus regarded as an extension of the CNS (London et al, 2013 ; Gupta et al, 2020 ; Rifai et al, 2021 ); retinal vascular lesions, including reduced arterial diameter, expanded venous diameter, and decreased fractional dimension, were found in patients with AD using fundus photographs (Cheung et al, 2014 ; McGrory et al, 2016 ). Moreover, accumulating evidence have reported that Aβ deposits were discovered in retinas of AD and animal studies (Hart et al, 2016 ; Doustar et al, 2017 ; den Haan et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the cerebral microvasculature is too small to be directly visualized in vivo . Due to the shared embryologic origin of the retina and brain, there is resemblance between blood-retinal barrier (BRB) and blood-brain barrier (BBB), and the retina is thus regarded as an extension of the CNS (London et al, 2013 ; Gupta et al, 2020 ; Rifai et al, 2021 ); retinal vascular lesions, including reduced arterial diameter, expanded venous diameter, and decreased fractional dimension, were found in patients with AD using fundus photographs (Cheung et al, 2014 ; McGrory et al, 2016 ). Moreover, accumulating evidence have reported that Aβ deposits were discovered in retinas of AD and animal studies (Hart et al, 2016 ; Doustar et al, 2017 ; den Haan et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…7 Studies of changes in neural retinal structure have been informative regarding changes in brain structure and function, and disease progression, in neurodegenerative diseases, 7 and accumulating evidence suggests that retinal microvasculature changes are also informative in cases of CNS disease. 3,[8][9][10][11] A brief and non-invasive method for assessing the state of retinal vasculature is optical coherence tomography angiography (OCTA). [12][13][14][15][16][17][18] OCT is a method based on lowcoherence interferometry that uses the difference between the power in spectral frequencies of near-infrared light reflected back from the eye, relative to the frequency composition of the original light output, to generate detailed images of retinal layers (conventional OCT) and the retinal microvasculature (OCTA), in a manner analogous to how ultrasound is used to generate biological images.…”
Section: Introductionmentioning
confidence: 99%
“…The use of OCTA in the field of neurology has generated data indicating that a wide range of neurodegenerative diseases are characterized by retinal microvasculature abnormalities, with extent of the alteration (eg, reduced density of vessels) often being correlated with disease severity. [9][10][11]19 OCTA is only now beginning to be incorporated into psychiatric studies, however. Previous studies of the retinal microvasculature in schizophrenia using conventional fundus photography have reported wider venules, 3,20 narrower arterioles, 20 and abnormal trajectories of venules and arterioles.…”
Section: Introductionmentioning
confidence: 99%
“…Three recent review articles have summarized OCT-A findings in AD patients [ 11 , 12 , 13 ]. Essentially, OCT-A examinations of AD retinas have shown an enlarged FAZ, a decrease of the vascular density of the superficial and deep vascular plexus in the macular region ( Figure 3 ), and also in the radial peripapillary capillary layer.…”
Section: Oct-a Findings In Neurological Diseasesmentioning
confidence: 99%